Faktor Rendahnya Keberhasilan Mediasi di Pengadilan Agama Sibuhuan Sebagai Solusi Memperbaharui Ketahanan Keluarga - Mahmudin Hasibuan; Erwin Harahap; Kalijunjung Hasibuan (Jurnal Teologi Islam, 2025)
This study aims to determine the Islamic legal view on mediation in divorce cases. And to determine the factors of low success of mediation in the Sibuhuan Religious Court. This study was conducted with the type of field research, using descriptive qualitative research methods. And the results, the Islamic legal view of mediation is known as as-sulhu, which is an agreement made by parties who agree to end their dispute. And in Islamic law the parties agree not to take legal action in resolving their dispute. And the factors of low success of mediation in the Sibuhuan Religious Court are internal factors between husband and wife because there is no common ground in the problems of husband and wife other than the word divorce or divorce. First because one of the two parties is already bored in marriage or the feelings of one of them have disappeared. And second, the state of the mediator who is less disciplined in resolving this case. and third, the husband and wife's family fully supports the divorce immediately